2014
DOI: 10.2355/isijinternational.54.2129
|View full text |Cite
|
Sign up to set email alerts
|

Interdiffusion in Co-Based Co–Al–W Ternary Alloys at Elevated Temperatures

Abstract: L12-type Co3(Al,W) compound is a very important phase in Co-based high temperature materials. This study investigated the interdiffusions of Co-based Co-Al-W ternary alloys at 1 423, 1 473 and 1 523 K. Two types of diffusion couples were employed to estimate four diffusivity matrix coefficients ( , , and ). A modified ternary Boltzmann-Matano method was employed for the evaluation of interdiffusion coefficients. The estimated cross-interdiffusion coefficients ( and ) had opposite signs at 1 523 K which is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 12 publications
0
1
0
Order By: Relevance
“…Cui et al [17] combined the available experimental data to develop composition-temperature dependent functions to describe the diffusion mobility in the Co-Al system for the FCC phase, following the methods outlined by Agren and co-workers. [18][19][20] The Co-W mobility functions in the FCC phase have been recently assessed by both Zhang et al [21] and Cui et al [22] Specific Al-W binary diffusion couple studies have not been reported, but both Chang et al, [9] Obata et al [23] Kobayashi et al [10] investigated the ternary Co-Al-W system in the FCC phase region in the temperature range from 900 to 1300°C. Other multicomponent diffusion-couple studies were conducted by G¢mez-Acebo et al [24] who studied the Al-Co-Cr-Ni-Ti system and by Minamino et al who studied the Co-Al-CrNi system.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Cui et al [17] combined the available experimental data to develop composition-temperature dependent functions to describe the diffusion mobility in the Co-Al system for the FCC phase, following the methods outlined by Agren and co-workers. [18][19][20] The Co-W mobility functions in the FCC phase have been recently assessed by both Zhang et al [21] and Cui et al [22] Specific Al-W binary diffusion couple studies have not been reported, but both Chang et al, [9] Obata et al [23] Kobayashi et al [10] investigated the ternary Co-Al-W system in the FCC phase region in the temperature range from 900 to 1300°C. Other multicomponent diffusion-couple studies were conducted by G¢mez-Acebo et al [24] who studied the Al-Co-Cr-Ni-Ti system and by Minamino et al who studied the Co-Al-CrNi system.…”
Section: Literature Reviewmentioning
confidence: 99%